A Gossip Politic
XV, 179 p. 27 illus., 3 illus. in color.
Keywords: This book makes explicit the historical, technological, and discursive links between gossip as a mode of communication, news media, and contemporary politics. A Gossip Politic advances a new framework of gossip, applying the informal understanding of the term to news talk and political actors. Authored by esteemed scholars in the fields of Political Science, Media Studies, Linguistics, and Sociology, chapters consider the influence of gossip on the press, the American presidency, and the public. A Gossip Politic provides readers with a multi-faceted portrait of the ways in which gossip has influenced media history, shaped our understanding of democracy, and contributed to our current political landscape. Andrea McDonnell is Associate Professor of Communication and Director of the Communication program at Providence College, USA, where her research examines the relationship between celebrity culture and media audiences. Adam Silver is Associate Professor of Political Science at Emmanuel College, USA, where his research focuses on the American Political Party Development, specifically the relationship between political elites and the electorate on the crafting of campaign strategy.